Pemanfaatan bokhasi paitan (Tithonia diversifolia) dan Bakteri Pelarut Fosfat (BPF) dalam budidaya tanaman jagung pada tanah pasca penambangan batuan - Cecep Hidayat; Yati Setiati Rachmawati; Noviana Herlina; Sofiya Hasani (Universitas Bangka Belitung, 2023)
Utilization postmine sandpits soil for maize cultivation can be done by improving soil fertility by applying organic matter and Phosphate Solubilizing Bacteria. This study aims to determine the effect of the application of bokashi paitan and Phosphate Solubilizing Bacteria on the improvement of soil fertility post mine sandpits soil, growth, and yield of maize. The study used a factorial randomized block design. The first factor was the concentration of PSB (0, 10, 20 ml plant-1) and the second factor was the dose of bokashi Tithonia diversifolia (0,10,20,30 t ha-1). The parameters observed were soil organic C, available P, RSR, leaf area, harvest index, and weight of corn without husks. The results showed that PSB inoculation increased C-organic and P-available, harvest index and weight of corn without husks. Application of bokashi paitan increases leaf area. PSB inoculation of 20 ml plant-1 improved soil C-organic and P-available as well as maize yields grown in post mine sandspits soil.